(untitled) (Asian Education Studies, 2023)
Enhancing informal learning through technology in museums is a relatively underdeveloped concept in China. This paper aims to investigate the potential of incorporating technology into ocean museums to facilitate informal learning from the perspective of an educator. The background of the museum and the existing challenges are discussed in detail, followed by the selection of suitable technologies and their rationale. The major theories guiding this approach are immersive learning, learning by doing, and productivity orientation.